2018
DOI: 10.1002/jcp.27639
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of heat shock transcription factor 1 in heart failure: A diagnostic approach

Abstract: Objective Nonexpression or expression inhibition of protective factors has been determined in the occurrence of heart failure (HF). Heat shock transcription factor 1 (HSF1) is among such factors, which reduces the incidence of HF by controlling cardiac hypertrophy and fibrosis. In this study, molecular mechanisms for nonexpression of HSF1 in HF patients have been investigated. Materials and methods This review paper is based on the material obtained via PubMed search of 1996–2018. The key search terms were "he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The multifunctional YB-1 is a highly conserved protein and can execute its effects mainly via its transcription regulation (29). Among the transcription factors, MEF2A, MEF2B, MEF2D, STAT3, GATA4, SOX9, SOCS3, HSF1, and YAP (20)(21)(22)(23)(24)(25)(26)(27) which play important roles in cardiomyopathies, we found that MEF2B was a downstream target of YB-1 in cardiomyocytes. MEF2B belongs to the MEF2 (Myocyte Enhancer Factor 2) family of transcription factors, which includes three additional members, MEF2A, MEF2C and MEF2D, is thought to play an important role in differentiation of cardiomyocytes (47).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The multifunctional YB-1 is a highly conserved protein and can execute its effects mainly via its transcription regulation (29). Among the transcription factors, MEF2A, MEF2B, MEF2D, STAT3, GATA4, SOX9, SOCS3, HSF1, and YAP (20)(21)(22)(23)(24)(25)(26)(27) which play important roles in cardiomyopathies, we found that MEF2B was a downstream target of YB-1 in cardiomyocytes. MEF2B belongs to the MEF2 (Myocyte Enhancer Factor 2) family of transcription factors, which includes three additional members, MEF2A, MEF2C and MEF2D, is thought to play an important role in differentiation of cardiomyocytes (47).…”
Section: Discussionmentioning
confidence: 90%
“…A few transcription factors, such as MEF2A, MEF2B, MEF2D, STAT3, GATA4, SOX9, SOCS3, HSF1, and YAP have been recently shown to play important roles in cardiomyopathies (20)(21)(22)(23)(24)(25)(26)(27). Therefore, we speculate that YB-1 may execute its protective effect in DCM by regulating some of the above-mentioned key transcription factors.…”
Section: Yb-1 Protects Against Diabetic Cardiomyopathy Via Transcriptional Suppression Of Mef2bmentioning
confidence: 91%
“…HSF1 is a transcriptional factor that interacts with heat shock element (HSE), a specific regulatory element located in promoter regions of the heat shock protein (HSP) genes [ 73 ]. The abnormal expression of HSF1 can promote cardiac injury in vascular pathologies; however, HSF1 has an important role in cellular protection from stress conditions [ 74 ]. NFκB is a nuclear transcription factor that regulates differential gene expressions affecting a broad spectrum of biological reactions including inflammation states, migration, apoptosis and cell proliferation [ 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, they promote the survival and resistance of tumor cells to treatments [20]. In the context of cardiovascular diseases, they protect the heart from stress damage [21]. HSTFs also play a role in inflammatory diseases [22], such as rheumatoid arthritis [23], affecting their severity and progression.…”
Section: Introductionmentioning
confidence: 99%